2015
DOI: 10.1002/cphc.201500926
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry at the Edge of Graphene

Abstract: The selective functionalization of graphene edges is driven by the chemical reactivity of its carbon atoms. The chemical reactivity of an edge, as an interruption of the honeycomb lattice of graphene, differs from the relative inertness of the basal plane. In fact, the unsaturation of the pz orbitals and the break of the π conjugation on an edge increase the energy of the electrons at the edge sites, leading to specific chemical reactivity and electronic properties. Given the relevance of the chemistry at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 129 publications
(380 reference statements)
2
93
0
2
Order By: Relevance
“…Previous studies carried out on clean graphene monolayer with a well-defined surface area, [230] on free-standing graphene samples over a nanopore, [231] and on graphene and graphite step edges using scanning electrochemical microscopy (SECM), [232,233] confirmed this trend that edges are electrochemically more active than the basal plane. [125] In combination with Raman spectroscopy (Fig. 8c), SECM is able to quantitatively correlate the defect density of graphene with its localized electrochemical activity (Fig.…”
Section: Graphene-based Electrochemical (Gec) Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies carried out on clean graphene monolayer with a well-defined surface area, [230] on free-standing graphene samples over a nanopore, [231] and on graphene and graphite step edges using scanning electrochemical microscopy (SECM), [232,233] confirmed this trend that edges are electrochemically more active than the basal plane. [125] In combination with Raman spectroscopy (Fig. 8c), SECM is able to quantitatively correlate the defect density of graphene with its localized electrochemical activity (Fig.…”
Section: Graphene-based Electrochemical (Gec) Biosensorsmentioning
confidence: 99%
“…Instead of providing an extensive list of the methods available to induce such modifications, we will continue with discussing a grafting strategy, frequently applied to covalently attach chemical moieties to graphene surface (or edges) via free-radical reactions. [27,28,109,[121][122][123][124][125] Graphene grafting uses alkyl or aryl diazonium salts as grafting agents, where the diazonium salt precursor is first chemically or electrochemically reduced (liberating nitrogen gas), to form a reactive alkyl or aryl radical that reacts with the aromatic system of the graphene sheet (the conductive channel of the transistor device fabricated on a 200 nm SiO 2 /highly doped Si substrate as shown in Figure 3c). [126] The disruption of the aromatic system by transforming the hybridization of carbon atoms from sp 2 to sp 3 results in a remarkable decrease in graphene conductivity, which can be controlled by reaction time (see also Table 2).…”
Section: Covalent Functionalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also evidenced from STM analysis that edges of graphene can exhibit higher electronic density of states (DOS) near Fermi level than the basal planes [70]. The edge configurations locally determine the distribution of electrons [71], and thus the selection of crystallographic orientation of graphene is of crucial importance for controlling its electronic properties in localized states. Zigzag and armchair are two main types of edges along the crystallographic directions in graphene.…”
Section: The Structure Of Graphenementioning
confidence: 99%
“…Hyun et al [87] further suggested that the edges of graphene flake have predominantly zigzag terminations below 400 °C, while the edges would be dominated by armchair and reconstructed zigzag edges above an annealing temperature of above 600 °C. Recent studies on the processes and mechanisms which drive the chemical functionalization of graphene edges are reviewed by Bellunato et al [71].
10.1080/14686996.2018.1494493-F0005Figure 5.(a) Scanning electron microscopy (SEM) image of a relatively large graphene crystal, which shows that most of the crystal’s faces are zigzag and armchair edges, as indicated by blue and red lines and illustrated in the inset [7].
…”
Section: The Structure Of Graphenementioning
confidence: 99%